Perbandingan Penggunaan Adjuvant Fentanyl 25µg Dan Klonidine 50µg Pada 10mg Bupivacain 0,5% Hiperbarik Terhadap Lama Kerja Blokade Sensorik Motorik Spinal Anestesi - Naufal Anasyi; Fransi Arsani; Mustoha Mustoha (Pusat riset dan Inovasi Nasional, 2022)
Surgery still often causes various problems, one of which is pain, but the problem of pain during and after surgery can be overcome by anesthesia technique. One of them is spinal anesthesia technique. However, spinal anesthesia still has drawbacks where the duration of sensory and motor blockade is still very short. Various methods are used to prolong the duration of sensory and motor blockade of spinal anesthesia, one of which is the addition of adjuvants such as fentanyl and clonidine. This study was conducted to compare the speed of onset of action of sensory-motor blockade and the lengthening of duration of action of sensory-motor blockade between the addition of 25 g fentanyl compared to 50 g conidine in 10 mg hyperbaric 0.5% bipivacaine administered under spinal anesthesia. This study used a Randomized Control Trial (RCT) design with a double-blind randomized control trial and was conducted at Mitra Plumbon Hospital Cirebon from March-April 2021. There were 42 patients who met the inclusion criteria who underwent surgery with spinal anesthesia. Patients were divided into 2 groups, group 1 used 10mg hyperbaric 0.5% bupivacaine plus 25µg fentanyl, while group 2 used 10mg hyperbaric 0.5% bupivacaine plus 50µg clonidine. We investigated the onset of action and duration of action of sensory-motor blockade, the effect of hemodynamic shock, the effect of sedation levels and intraoperative adverse effects (side effects). Data analysis using SPSS 20.0. In the group of 10 mg bupivacaine 0.5% hyperbaric plus clonidine 50 g, the onset of action of sensory-motor blockade was faster and the duration of action was longer than in the group of 10 mg bupivacaine 0.5% hyperbaric plus 25 g fentanyl with a P value <0.05. Likewise, the effect of hemodynamic fluctuations in the 10mg hyperbaric 0.5% bupivacaine group plus 50 g clnidine was more stable than the 10mg hyperbaric 0.5% bupivacaine group plus 25 g fentanyl. While the effect of the level of sedation and intraoperative side effects are comparable